2018
DOI: 10.1080/10934529.2018.1438825
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metal oxide nanoparticles on nitrification in wastewater treatment systems: A systematic review

Abstract: While the variety of engineered nanoparticles used in consumer products continues to grow, the use of metal oxide nanoparticles in electronics, textiles, cosmetics and food packaging industry has grown exponentially in recent years, which will inevitably result in their release into wastewater streams in turn impacting the important biological processes in wastewater treatment plants. Among these processes, nitrification play a critical role in nitrogen removal during wastewater treatment, however, it is sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 115 publications
0
7
0
Order By: Relevance
“…Metal oxide engineered nanomaterials (ENMs) are commonly used in various industrial applications and daily consumer goods including sunscreens (Burnett and Wang, 2011), cosmetic products (Lu et al, 2015), antimicrobial coatings (Raghunath and Perumal, 2017), solar cells (Singh et al, 2016), semiconductors (Jo et al, 2015), pigments and UVabsorption filters (Singh and Nanda, 2014;Kim and Min, 2013), filling materials in food production (Kapoor et al, 2018), as well as toothpastes, and sanitary ware coatings (Contado, 2015). In spite of the widely publicized benefits of metal oxide ENMs, recent concerns have been raised regarding potential adverse effects of these ENMs on human health and the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Metal oxide engineered nanomaterials (ENMs) are commonly used in various industrial applications and daily consumer goods including sunscreens (Burnett and Wang, 2011), cosmetic products (Lu et al, 2015), antimicrobial coatings (Raghunath and Perumal, 2017), solar cells (Singh et al, 2016), semiconductors (Jo et al, 2015), pigments and UVabsorption filters (Singh and Nanda, 2014;Kim and Min, 2013), filling materials in food production (Kapoor et al, 2018), as well as toothpastes, and sanitary ware coatings (Contado, 2015). In spite of the widely publicized benefits of metal oxide ENMs, recent concerns have been raised regarding potential adverse effects of these ENMs on human health and the environment.…”
Section: Introductionmentioning
confidence: 99%
“…AOB 16S-rRNA), and the decreased abundance of the active players in wastewater N-removal is often found to correlate with nitrification inhibition. Coupling different types of techniques is more frequently adopted in recent studies, and this will eventually provide a holistic picture of ENP effects on the nitrification process in WWTPs (Kapoor et al, 2018). At the current stage, many gaps remain to establish meaningful and unambiguous connections between performance deterioration data and cellular and molecular damaged data.…”
Section: Methods and Assays For Enp Toxicity Assessmentmentioning
confidence: 99%
“…The increasing use of NPs in daily products leads to their release in WWTPs and natural systems. Although the environmental concentrations of NMs are still unknown, there is evidence of the presence of NPs in WWTPs [27], from which some of them escape into water bodies [28]. NPs may remain in the environment for a long period and can be potentially toxic to aquatic life [28].…”
Section: Hrt and Zno Nps Effect On Algal Growthmentioning
confidence: 99%
“…It is important to assess the effects of metal nanoparticles on nutrient removal in biological wastewater treatment processes [27]. During the exposure of S. rubescens to ZnO NPs, it was observed that nutrient removal was analogous to biomass concentration, and nutrient uptake was not affected by the presence of NPs.…”
Section: Zno Nps Effects On Algal Nutrients Uptake and Lipid Accumulamentioning
confidence: 99%
See 1 more Smart Citation